2011
DOI: 10.1021/nl200150p
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Carbon Nanotube Band Gaps through Leakage Current and Excitonic Transitions of Nanotube Diodes

Abstract: The band gap of a semiconductor is one of its most fundamental properties. It is one of the defining parameters for applications, including nanoelectronic and nanophotonic devices. Measuring the band gap, however, has received little attention for quasi-one-dimensional materials, including single-walled carbon nanotubes. Here we show that the current-voltage characteristics of p-n diodes fabricated with semiconducting carbon nanotubes can be used along with the excitonic transitions of the nanotubes to measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…The intrinsic electronic band gap of the nanotube should be 1.48 eV according to Eq. (2). With the diameter of 0.9 nm, calculation by either Eq.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The intrinsic electronic band gap of the nanotube should be 1.48 eV according to Eq. (2). With the diameter of 0.9 nm, calculation by either Eq.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the many-body theory gives a very different result [6,[12][13][14][15], predicting an appreciably larger band gap for a semiconductor nanotube than that predicted by the one-particle model [5]. The many-body picture has been verified by plenty of optical experiments to date [2][3][4][5][6]. In this context, the interpretation of STS of carbon nanotubes seems not so simple.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the case of a p-n junction reverse bias current is due to the diffusion current from minority carriers and/or the generation of electron hole pairs in the junction. An ideality factor of 1 represents a saturation current due to diffusion current and an ideality factor of 2 represents a saturation current due to generation current, if η > 2, this indicates the junction does not behave as an ideal p-n junction [11,37,39]. In symmetrically contacted CNT p-n junctions formed by a split gate Malapanis et al showed that I 0 decreased exponentially with increasing CNT bandgap [11].…”
Section: Asymmetric Contact Devicementioning
confidence: 99%
“…has been used to demonstrate CNT field effect transistor (FET) p-n junction diodes [3,[8][9][10][11]. It can also be used to modify the band profile of CNTs to facilitate EL.…”
Section: Introductionmentioning
confidence: 99%